A potential role for somatostatin signaling in regulating retinal neurogenesis - Kurt Weir (Nature Portfolio, 2021)
Abstract Neuropeptides have been reported to regulate progenitor proliferation and neurogenesis in the central nervous system. However, these studies have typically been conducted using pharmacological agents in ex vivo preparations, and in vivo evidence for their developmental function is generally lacking. Recent scRNA-Seq studies have identified multiple neuropeptides and their receptors as being selectively expressed in neurogenic progenitors of the embryonic mouse and human retina. This includes Sstr2, whose ligand somatostatin is transiently expressed by immature retinal ganglion cells. By analyzing retinal explants treated with selective ligands that target these receptors, we found that Sstr2-dependent somatostatin signaling induces a modest, dose-dependent inhibition of photoreceptor generation, while correspondingly increasing the relative fraction of primary progenitor cells. These effects were confirmed by scRNA-Seq analysis of retinal explants but abolished in Sstr2-deficient retinas. Although no changes in the relative fraction of primary progenitors or photoreceptor precursors were observed in Sstr2-deficient retinas in vivo, scRNA-Seq analysis demonstrated accelerated differentiation of neurogenic progenitors. We conclude that, while Sstr2 signaling may act to negatively regulate retinal neurogenesis in combination with other retinal ganglion cell-derived secreted factors such as Shh, it is dispensable for normal retinal development.